Frontiers in geochemistry : contribution of geochemistry to the study of the earth - Harmon, R. S. (Russell S.); Parker, A. (Andrew), 1941-; Wiley InterScience (Online service) (Chichester, West Sussex ; Hoboken, N.J. : Wiley-Blackwell, 2011)
'This is a unique collection of reviews of the significance of geochemistry in the earth sciences, with contributions from a range of internationally distinguished scientists. It deals with both the historical contribution (Part 1) and the current and likely future importance of the subject in dealing with key environmental issues (Part 2) The book is based on contributions given to the 2008 IGC session with same name: Provides the most comprehensive review of the scope and achievements of modern geochemistry in a form accessible to and affordable by students (advanced undergraduates and graduates) The contributors are all world leaders in their particular field Co-published with the IAGC - the worlds premiere learned society for the geochemistry community. The only affordable and single-volume overview of the entire subject.'--
'The book will be based on contributions given to the 2008 IGC session with same name'--
Front Matter -- Colour Plates -- Contribution of Geochemistry to the Study of the Earth. Geochemistry and Secular Geochemical Evolution of the Earth's Mantle and Lower Crust / Balz S Kamber -- Crustal Evolution b6 (BA Mineral Archive Perspective / C J Hawkesworth, A I S Kemp, B Dhuime, C D Storey -- Discovering the History of Atmospheric Oxygen / Heinrich D Holland -- Geochemistry of the Oceanic Crust / Karsten M Haase -- Silicate Rock Weathering and the Global Carbon Cycle / Sigurdur R Gislason, Eric H Oelkers -- Geochemistry of Secular Evolution of Groundwater / Tomas Paces -- Stable Isotope Geochemistry: Some Perspectives / Jochen Hoefs -- Frontiers in Geochemistry. Geochemistry of Geologic Sequestration of Carbon Dioxide / Yousif K Kharaka, David R Cole -- Microbial Geochemistry: At the Intersection of Disciplines / Philip Bennett, Christopher Omelon -- Nanogeochemistry: Nanostructures and their Reactivity in Natural Systems / Yifeng Wang, Huizhen Gao, Huifang Xu -- Urban Geochemistry / Morten Jartun, Rolf Tore Ottesen -- Archaeological and Anthropological Applications of Isotopic and Elemental Geochemistry / Henry P Schwarcz -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: Geochemistry -- Congresses; Geology; Science; SCIENCE -- Geophysics; Geochemistry; Electronic books; Conference papers and proceedings